SAT0037 The effects of b cell directed therapy on disease relevant biomarkers in subjects at risk of rheumatoid arthritis. (15th June 2017) - Gerlag, D; Safy, M; Maijer, K; Ramwadhdoebe, T; Tas, S; Vries, N de; Starmans-Kool, M; Tubergen, A van; Janssen, M; Eyre, S; Klareskog, L; Zwinderman, K; et al.
Abstract : Background: Exploration of the mechanism underlying the delay of development of clinical signs of seropositive rheumatoid arthritis (RA) observed after B cell directed therapy in individuals at risk of developing autoantibody positive RA may offer insights into the mechanism of disease and may assist the development of preventive strategies. Objectives: To explore the effects of a single infusion of rituximab (anti-CD20 antibody) on the observed delay of the onset of clinically manifest arthritis in individuals at risk of developing autoantibody positive RA. Methods: In a study of 81 subjects positive for both anti-citrullinated protein antibodies (ACPA) and rheumatoid factor (RF) with arthralgia who never had clinically manifest arthritis and never used disease-modifying antirheumatic drugs, a 55% reduction of the risk of developing arthritis was observed 12 months after receiving a single iv infusion of 1000 mg rituximab when compared to placebo. In this group there was a delay in the development of arthritis of 12.0 months (12 months placebo vs 24 rituximab group) at the 25% quartile (75% free of arthritis) of the cumulative arthritis-free survival. Explorative analysis of disease-related biomarkers was performed in subgroups to better understand the mechanisms of the observed delay of clinical disease onset. Results: Baseline levels of ESR (mm/h; HR 1.03; p=0.016), the total number of B cells in peripheral blood (HR 1.48; p=0.047), the presence of anti-alpha-enolase 1 (anti-CEP1) antibodies (HR 3.71; p=0.004) and the percentage of regulatory B cells (HR 1.04; p=0.002) were related to arthritis development over time. Importantly, genetic analysis of 100 RA associated SNPs showed that the top SNP associated with arthritis development in the rituximab-treated group (OR=7, MAF in cases 60% compared to 17% in unaffected) was in the PLCL2 gene, described to play a role in B cell signaling 1 . In individuals treated with rituximab, B cell numbers and subtypes mainly of the memory and regulatory compartment as well as serum levels of IgM-RF (p<0.0001), IgA-RF (p=0.003), total IgM (p=0.001), and anti-CCP (p=0.035) showed statistically significant changes over time compared to individuals who received placebo. Exploratory analysis showed trends for multiple biomarkers in the B cell compartment that appeared predictive of the development of arthritis. Conclusions: A single infusion of 1000 mg rituximab significantly affects B cell numbers and subsets of memory and regulatory B cells as well as a reduction of disease-related antibodies and immunoglobulin levels in individuals at risk of RA. The changes coincide with a decrease in risk and a delay in development of arthritis in this population. PLCL2 gene polymorphism was associated with arthritis development in rituximab-treated individuals. References: Takenaka K, Fukami K, Otsuki M, Nakamura Y, Kataoka Y, Wada M, Tsuji K, Nishikawa S, Yoshida N, Takenawa T. Role of phospholipase C-L2, a novel phospholipase C-like protein that lacks lipase activity, in B-cell receptor signaling. Mol Cell Biol. 2003 Oct;23(20):7329–38. Disclosure of Interest: None declared